Maxillofacial Fractures in a Hospital in the State of Chiapas, Mexico: Cross Sectional Study - Nájera-Ortiz, Juan Carlos (2025)
Fractures of the maxillofacial complex represent one of the most relevant health challenges at present, given their high incidence and cost to public health. In order to analyze the management of maxillofacial fractures treated in a public hospital in Chiapas, Mexico, during 2022, a cross-sectional study was carried out through interviews, clinical reviews, and records of patients treated with some type of maxillofacial fracture during the study period in the aforementioned hospital. The necessary information was obtained to meet the objectives. The main etiology was traffic accidents (65.9%). The main affected area was the lower third of the face (65.9%). A statistical association was found between the imaging study used, fracture treatment, specialist intervention, and type of patient management with the anatomical area of the fracture. Therefore, the epidemiological characteristics found were similar to those reported in the international literature. The management given to the fractures was according to their location.